Analisis Kualitas Anggaran Pendapatan Dan Belanja Daerah Kabupaten Mimika Tahun 2018-2021 - Yundy Hafizrianda; Ida Ayu Purba Riani; Agustinus Salle (Universitas Cenderawasih, 2022)
This study aims to: (1) measure and analyze the performance of APBD management in Mimika Regency; (2) evaluate and analyze the quality of the Mimika Regency APBD; and (3) formulate recommendations for better quality APBD management policies in the future that can provide impetus for the acceleration of Mimika Regency's socio-economic development. The approach used in this study is a quantitative approach, in which the APBD quality assessment refers to eight APBD performance indicators measured using an ordinal scale and a composite index to obtain a value for the quality of APBD management in a given year. The results of data processing show that in 2018, the quality value of the Mimika Regency APBD only reached 72.92 points, which was included in the